Physical Activity and Postmenopausal Breast Cancer Risk in the NIH-AARP Diet and Health Study - Peters, Tricia M. (2009)
BACKGROUND: Although physical activity has been associated with reduced breast cancer risk, whether this association varies across breast cancer subtypes or is modified by reproductive and lifestyle factors is unclear. METHODS: We examined physical activity in relation to postmenopausal breast cancer risk in 182,862 U.S. women in the NIH-AARP Diet and Health Study. Physical activity was assessed by self-report at baseline (1995–1996), and 6,609 incident breast cancers were identified through December 31, 2003. Cox regression was used to estimate the relative risk (RR) and 95% confidence interval (95% CI) of postmenopausal breast cancer overall and by tumor characteristics. Effect modification by select reproductive and lifestyle factors was also explored. RESULTS: In multivariate models, the most active women experienced a 13% lower breast cancer risk versus inactive women (RR, 0.87; 95% CI, 0.81–0.95). This inverse relation was not modified by tumor stage or histology but was suggestively stronger for estrogen receptor (ER)-negative (RR, 0.75; 95% CI, 0.54–1.04) than ER-positive (RR, 0.97; 95% CI, 0.84–1.12) breast tumors and was suggestively stronger for overweight/obese (RR, 0.86; 95% CI, 0.77–0.96) than lean (RR, 0.95; 95% CI, 0.87–1.05) women. The inverse relation with physical activity was also more pronounced among women who had never used menopausal hormone therapy and those with a positive family history of breast cancer than their respective counterparts. CONCLUSIONS: Physical activity was associated with reduced postmenopausal breast cancer risk, particular to ER-negative tumors. These results, along with heterogeneity in the physical activity-breast cancer relation for subgroups of menopausal hormone therapy use and adiposity, indicate that physical activity likely influences breast cancer risk via both estrogenic and estrogen-independent mechanisms.